2013
DOI: 10.1055/s-0032-1333261
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Accumulation Product is Related to Metabolic Syndrome in Women with Polycystic Ovary Syndrome

Abstract: • ▶ polycystic ovary syndrome • ▶ metabolic syndrome • ▶ lipid accumulation product Lipid Accumulation Product is Related to Metabolic Syndrome in Women with Polycystic Ovary Syndrome are exposed to risk factors at a younger age [ 9 ] . Early and accurate identifi cation of high-risk individuals for MS could be important to predict and prevent CVD and type 2 diabetes. There is, therefore, an urgent need to develop a simple, accurate and economic predictor for MS in PCOS. The lipid accumulation product (LAP), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 11 publications
5
33
0
1
Order By: Relevance
“…35 If we take into consideration that BMI was not shown to be an accurate predictor of the risk of obesity-related diseases, 36 our results are in line with other studies that found WC to be an important clinical predictor of the MetS in respective PCOS populations. 10,16 Our results, obtained three international criteria for the MetS, are in line with the results of other authors attributing to the WC a high accuracy of prediction of MetS irrespectively of the cut-off values for WC. Although our data showed that WC and BMI shared the same level of accuracy, WC had higher sensitivity in predicting MetS, particularly when the IDF and JIS criteria are used.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…35 If we take into consideration that BMI was not shown to be an accurate predictor of the risk of obesity-related diseases, 36 our results are in line with other studies that found WC to be an important clinical predictor of the MetS in respective PCOS populations. 10,16 Our results, obtained three international criteria for the MetS, are in line with the results of other authors attributing to the WC a high accuracy of prediction of MetS irrespectively of the cut-off values for WC. Although our data showed that WC and BMI shared the same level of accuracy, WC had higher sensitivity in predicting MetS, particularly when the IDF and JIS criteria are used.…”
Section: Discussionsupporting
confidence: 91%
“…21,23,29 Among women with PCOS, low HDL was confirmed in many studies and shown to be one of the most frequent among single abnormalities in MetS. 9,15,16,25,28,37 Our results confirmed an abnormal HDL concentration within a selected cohort of Europid women with PCOS and MetS. Furthermore, HDL was shown to be an accurate marker, and together with LAP, the one most powerfully associated with MetS using either NCEP-ATP III, IDF or JIS criteria.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations